Sensory and Nutritional Characterization of Six Different Types of Croatian Traditional Meat Product Characterization of Croatian Traditional Meat Products - Nina Kudumija; Ivica Kos; Tina Lešić; Nada Vahčić; Ana Vulić; Tomaž Polak; Greta Krešić; Ivan Vnučec; Darija Bendelja Ljoljić; Mario Škrivanko; Tanja Bogdanović; Jelka Pleadin (Journal of Food Quality)
The aim of this study was to determine quality parameters of Croatian traditional meat products (TMPs) via the analysis of their sensory and nutritive parameters, including physicochemical properties, fatty acid profile, mineral content, and amino acid composition. Over 2020 and 2021, a diverse collection of 242 dry-fermented sausages and dry-cured TMPs from various rural households was assessed. Sensory evaluations highlighted their satisfactory qualities, with moderate salinity and a unique taste profile characterized by a slight bitterness, with low sweetness and sourness levels. Detailed analyses revealed significant differences (p<0.05) across samples in key parameters such as water activity, pH, moisture, ash, fat, protein, carbohydrate, and NaCl content, as well as in the fatty acid profile and mineral content, underscoring the diversity and richness of these products. Amino acids such as alanine, histidine, isoleucine, leucine, and proline were present in high amounts in all samples, largely varying in their content within the same product type. The findings underscore the high quality and distinctiveness of Croatian TMPs, attributed to varied recipes and production techniques across different regions, suggesting the potential for standardization and further quality enhancement. Despite the presence of saturated fats and salt, the nutritional value of these TMPs, marked by high protein content and essential minerals, aligns with health-conscious consumer trends, presenting an opportunity for increased global appreciation of these artisanal products. The positive results from the sensory analysis underscore the TMPs' ability to align with consumer taste preferences, thereby affirming their reputation as a national delicacy. This could represent a promising direction for future research, focusing on the refinement of production and marketing strategies to attract a global audience, especially those with a preference for health-conscious and traditional culinary options.